Analisis Model CAPM dan APT Dalam Memprediksi Tingkat Return Saham Syariah (Studi kasus Saham di Jakarta Islamic Index ) - Lemiyana Lemiyana (I-Finance Journal, 2015)
The aim of  this research is to recognize the accuracy of CAPM and APT models in predicting the stock return of rural stocks and conventional stock at Jakarta Islamic Index.  Variable of this research are JII stock return, Beta, Risk free, Market return, GDP, SBI and inflation.  The analysis tools that used to measure macro economics variables in the future is Autogrssive Integrated Moving Avarage (ARIMA).  The accuracy of CAPM and APT models is measured by standart deviation and t test is used to compare the accuracy between CAPM and APT models.  The population of this research is all monthly stock return Jakarta Islamic Index.  Whereas the sample used is the monthly stock return of 11 JII companies during 2007 – 2012.  The result of this research showes that the CAPM model is more accurate than APT model in predicting the stock return Jakarta Islamic Index. Keywords: Stock Return, Beta, Risk free, Market return, GDP, SBI,and  Inflation